IDENTIFIKASI KERUSAKAN TUMBUHAN INANG OLEH PARASIT Dendtopthoepentandra (L.) Miq. (Loranthaceae) : SEBUAH STUDI KASUS DITAHURA BENGKULU - Sunaryo Sunaryo (BERITA BIOLOGI, 1998)
The Mistletoe o/Dendrophthoe pentandra (Loranthaceae) growing on several plant collection at Taman Hutan Raya Bengkulu.Thirty one infected and uninfected branches of five host species were observed, i.e.Archidendron bubalinum(Leguminosae),Rhodamnia cinerea (Myrtaceae),Dillenia excelsa (Dilkniaceae),Aporosa aurita (Euphorbiaceae) and'Vitex pinnata (Verbenaceae).The results showed that the host tissue can be destroyed through penetration and development of primer haustorium.Moreover, in the natural conditions, the mistletoe causes degradation of the distal part of the infected branches.